(untitled) (Baghdad Science Journal, 2025)
In this research, optical communication coding systems are designed and constructed by utilizing Frequency Shift Code (FSC) technique. Calculations of the system quality represented by signal to noise ratio (S/N), Bit Error Rate (BER),and Power budget are done. In FSC system, the data of Nonreturn- to–zero (NRZ ) with bit rate at 190 kb/s was entered into FSC encoder circuit in transmitter unit. This data modulates the laser source HFCT-5205 with wavelength at 1310 nm by Intensity Modulation (IM) method, then this data is transferred through Single Mode (SM) optical fiber. The recovery of the NRZ is achieved using decoder circuit in receiver unit. The calculations of BER and S/N for FSC system at maximum fiber length at 61.2 km equal to 2.30551×10-12, 47.88526 dB respectively. The power budget for FSC system was calculated to be 29 dB. Results show that the BER increases when the received optical power decreases the due to increase of the optical fiber length61.2 km. while S/N decreases. The optical power budget increases as the transmitted optical power increases.